Are semantic and phonological fluency based on the same or distinct sets of cognitive processes? Insights from factor analyses in healthy adults and stroke patients. (May 2017) - Schmidt, Charlotte S.M.; Schumacher, Lena V.; Römer, Pia; Leonhart, Rainer; Beume, Lena; Martin, Markus; Dressing, Andrea; Weiller, Cornelius; Kaller, Christoph P.
Abstract: Verbal fluency for semantic categories and phonological letters is frequently applied to studies of language and executive functions. Despite its popularity, it is still debated whether measures of semantic and phonological fluency reflect the same or distinct sets of cognitive processes. Word generation in the two task variants is believed to involve different types of search processes. Findings from the lesion and neuroimaging literature further suggest a stronger reliance of phonological and semantic fluency on frontal and temporal brain areas, respectively. This evidence for differential cognitive and neural contributions is, however, strongly challenged by findings from factor analyses, which have consistently yielded only one explanatory factor. As all previous factor-analytical approaches were based on very small item sets, this apparent discrepancy may be due to methodological limitations. In this study, we therefore applied a German version of the verbal fluency task with 8 semantic (i.e. categories) and 8 phonological items (i.e. letters). An exploratory factor analysis with oblique rotation in N=69 healthy young adults indeed revealed a two-factor solution with markedly different loadings for semantic and phonological items. This pattern was corroborated by a confirmatory factor analysis in a sample of N=174 stroke patients. As results from both samples also revealed a substantial portion of common variance between the semantic and phonological factor, the present data further demonstrate that semantic and phonological verbal fluency are based on clearly distinct but also on shared sets of cognitive processes. Highlights: Semantic and phonological fluency rely on distinct cognitive and neural processes. Previous factor analyses however revealed only one single explanatory factor. Present analyses in healthy adults and stroke patients resolve this discrepancy. Results in both samples reveal distinct yet shared sets of cognitive processes.